Gadget Dependency among Medical College Students in Delhi - Gupta, N; Krishnamurthy, V; Majhi, J; Gupta, S (Indian Journal of Community Health, 2013)
Background: Gadget holds the great importance in everyday life. Mobile phone and internet usage have become universal practice especially among the student community. Gadgets usage has both pros and cons. Objective: To assess the magnitude of gadget utilization among medical college students in Delhi and to estimate the burden of gadget dependency. Methodology: A cross sectional study was conducted in three medical colleges. The participants were 957 medical students selected by systematic random sampling, interviewed using a self-administered questionnaire. Result: The sample consisted of 485 (50.7%) males and 472 (49.3%) females, aged 17-25 years. Gadgets of at least one variety were uniformly used by all the students, 22.4% of the students surveyed were found to be gadget dependent. Conclusion: Our study shows high prevalence of gadget dependency among medical students. There is need to create awareness regarding the problem of gadget dependency and its social and health effects.